ANALISIS TINGKAT PARTISIPASI MASYARAKAT DALAM MENDUKUNG EFEKTIVITAS PROGRAM MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DI NEGERI, NEGERI LIMA KECAMATAN LEIHITU, MALUKU TENGAH - Zadrak Holberth Punjanan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Rural development requires active community participation as the main actor. The Development Planning Deliberation (Musrenbang) is organized as a strategic forum to channel public aspirations; however, in practice, a gap often exists between planning and implementation. This study aims to analyze the level of community participation and assess the effectiveness of the Musrenbang program implementation in Negeri Lima, Leihitu District, Central Maluku. A descriptive quantitative approach was employed using a Likert-scale questionnaire distributed to 47 respondents from various community elements, supplemented by observation and interviews. The results indicate that the community's participation level remains at the tokenism stage, where public proposals tend to be formalities and do not significantly influence decision-making. Meanwhile, the effectiveness of the Musrenbang implementation scored 72%, falling into the